Construction of analytical wave solutions to the conformable fractional dynamical system of ion sound and Langmuir waves. Issue 6 (2nd November 2022) - Younas, U.; Seadawy, Aly R.; Younis, M.; Rizvi, S.T.R.
ABSTRACT: In this article, the exact wave structures are discussed to conformable time-fractional system of ion sound under influence of ponderomotive force. It is caused by non-linear force and is experienced by a charged particle in an oscillating electromagnetic field (EMF) of inhomogeneity. It is investigated that system exhibits the trigonometric, hyperbolic and exponential function solutions including some special known solitary, shock, singular, single and mixed solitons. The strategy that is used to extract the wave structures for this ionic system of Langmuir waves is known as generalized exponential rational function method. Moreover, the constraint conditions are also reported which validate the existence of solutions. Furthermore, 3-dimensional, 2-dimensional and corresponding contour graphs are presented for the physical movement of the earned solutions under the appropriate selection of the parameters. The obtained results are helpful for understanding of the study of wave propagation and are also vital for numerical and experimental verification in plasma physics.